Workplace Bullying and Depressive Symptoms among Employed Women in Pakistan: A Cross-Sectional Study - Feroz Usmani,; Aslam, Amna; Farah Kanwal, (International "Journal of Academic Research for Humanities", 2023)
This research was conducted to investigate the relationship between workplace bullying and depressive symptoms among employed women in Pakistan. Correlational quantitative research was conducted on 135 working females. Data was collected using a simple random sampling from various public and private organizations in Lahore (Kinnaird College for Women and Services Hospital). Participants filled Demographic Sheet, Workplace Bullying Scale, and Major Depression Inventory. In the data set four categories of age groups were found (54.8%) of participants were lying in the 20-25 years range, (22.2%) were 25-30 years, (10.4%) lay in the 30-35 years, and (12.6%) lie in 35-40 category. 95 participants were single and 40 were married. Pearson correlation and regression analysis revealed that workplace bullying and depressive symptoms have a significant positive correlation. (r= .682, p<0.01). The results indicate that individuals who face bullying at their workplace are more likely to develop depressive symptoms. Person-related bullying (personal attacks) is more commonly observed than work-related bullying (professional damage) in working women. The significance of research lies in shedding light on the escalating problem of workplace bullying among women in South Asian countries, with a focus on Pakistan. Understanding the prevalence, forms, and consequences of workplace bullying is to create awareness and implement effective interventions. The present study found significant marital status differences in the development of depressive symptoms due to workplace bullying. The results obtained indicated that there is a positive correlation between workplace bullying and depressive symptoms. The results also unmarried women face more workplace bullying than married women.